Numerical Investigation on Flexural Buckling Behavior of Hot-rolled Steel Columns at Elevated Temperatures - Nemer, Samer; Papp, Ferenc (Periodica Polytechnica Civil Engineering, 2021)
In this paper, a numerical investigation on the global buckling capacity of the axially compressed steel columns with hot-rolled I cross-section at elevated temperatures is presented. Geometrically and materially non-linear finite element model and the ABAQUS software were used to determine the buckling resistance. The numerical ABAQUS model was validated using experimental results available in the literature, and then the validated numerical model was used to generate a database of load-carrying capacity. The parametric study covered three different cross-section classes (class 1, 2 and 3), ten different non-dimensional slenderness ̄λ = 0.5, 0.6, 0.7, 0.9,1,3,5,7,9, 2.0), three different temperatures (400°C, 500°C, 600°C), and two stress-strain constitutive relations including (the nonlinear material model adopted in the European guidance for structural fire design EN1993-1-2, and a Bilinear material model), with and without residual stress. The influence of the model parameters on the load capacity of steel columns at elevated temperatures was evaluated. The results of the parametric study were compared with the results of the simplified calculation model presented in EN1993-1-2.